Agronomic evaluation and nutritional value of Morera (Morus alba) - Zapatier Santillan, David Aurelio (2021)
Agronomic behavior and nutritional value of Morus alba were evaluated at different ages. The variables for agronomic behavior: plant height (PH) (m); leaf biomass per plant (LBP g MS plant-1); stem biomass per plant (SBP g MS plant-1); leaf / stem ratio grams (SRG/ T g); forage biomass per plant (FBP) (g); productivity (Prod) (t MS ha-1). Chemical composition: dry matter (DM); organic matter (OM); crude protein (CP); neutral detergent fiber (NDF) and acid detergent fiber (ADF). In vitro digestibility: dry matter (IVDDM); organic matter (IVDOM); neutral detergent fiber (IVDNDF) and acid detergent fiber (IVDADF). Treatments: T1: Morus alba 40 days of harvest; T2: Morus alba 55 days of harvest; T3: Morus alba 70 days of harvest; T4: Morus alba 85 days of harvest. A Complete Random Design with four treatments and four repetitions was used. The highest (P <0.05) PH and LBP was presented by T3 and T4 (1.50 and 1.67 m) and (179.68 and 169.44 g DM plant-1), the FBP and Prod. were registered by T4 and T3 (433, 36 and 369.37 g DM plant-1) and (7.68 and 6.55 t DM ha-1), the BTP was recorded by T4 (263.92 g DM plant-1), the RHT was reported by T2 (1, 17 g). The highest (P <0.05) DM and CP registered T4 and T1 (33.81 and 22.17%). The IVDDM, IVDOM, IVDNDF and IVDADF (P <0.05) was recorded in T1 (68.07; 65.75; 62.98 and 44.91%). The harvest age influences the agronomic behavior and its nutritional value.